Possibilities of using Mobile Technologies in the Educational Process - Ismoilova Mahsuma Narziqulovna (International Journal on Integrated Education, 2023)
The revolutionary changes taking place in our rapidly developing society today require the widespread use of technical means that ensure adequate use of information in the educational process. It is relevant today to use mobile gadgets in the learning process in order to solve all kinds of pedagogical problems. The reasons for using mobile devices in education are many. For example, at any time, regardless of location, you can engage in self-education; a game form that arouses more interest than classical organizational forms of learning; the ability to accurately control attendance; the possibility of conducting a “five-minute” knowledge control, the possibility of taking independent and homework in electronic form, which forces all students to prepare for each lesson; the ability to collect statistical data, analyze the dynamics of mastering educational material from different positions: each student, the whole group, academic subject, teacher; more efficient exchange of important information between participants in the educational process and others. This article talks about the possibilities of mobile applications in education and the thoughts of great scientists about technical means in the educational process.